2017
DOI: 10.1016/j.abb.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The chemical biology of HNO signaling

Abstract: Nitroxyl (HNO) is a simple molecule with significant potential as a pharmacological agent. For example, its use in the possible treatment of heart failure has received recent attention due to its unique therapeutic properties. Recent progress has been made on the elucidation of the mechanisms associated with its biological signaling. Importantly, the biochemical mechanisms described for HNO bioactivity are consistent with its unique and novel chemical properties/reactivity. To date, much of the biology of HNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 78 publications
3
33
0
1
Order By: Relevance
“…Nitroxyl (azanone, nitroxyl hydride, HNO) has gained increasing attention owing to a growing number of reports describing its biological activity. The properties of HNO show some similarities to those of its redox sibling NO, but major differences are also observed . In particular, HNO is showing promise for treating heart failure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroxyl (azanone, nitroxyl hydride, HNO) has gained increasing attention owing to a growing number of reports describing its biological activity. The properties of HNO show some similarities to those of its redox sibling NO, but major differences are also observed . In particular, HNO is showing promise for treating heart failure .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, HNO is showing promise for treating heart failure . Although HNO has been the subject of extensive experimental and theoretical analysis, there remains much to learn about its chemistry, reactivity and biological activity. One of the main challenges in studying the reactivity of HNO is its rapid dimerization to nitrous oxide and water in aqueous solution ( k =8×10 6 m −1 s −1 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Using a HNO donor (Angeli's salt), Andrews et al [131] demonstrated for the first time that it acts through the sGC/cGMP pathway. HNO also protects PUFA from peroxidation due to its antioxidant properties [132]. The protective ability of HNO should also be considered in the case of the sperm plasma membrane, as it contains a high amount of PUFA [73].…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%
“…The protective ability of HNO should also be considered in the case of the sperm plasma membrane, as it contains a high amount of PUFA [73]. On the other hand, HNO can increase intracellular levels of H 2 O 2 by inhibiting its degradation, and it also reacts with thiol proteins, such as GAPDH, decreasing its activity [132,133]. Sperm-specific GAPDH (GAPDS) is particularly important in sperm cell energetic metabolism [68].…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%
“…Nitric oxide (NO) is an important signaling molecule that plays a key role in numerous physiological processes, such as vasodilation, immune response, neuronal signaling, etc . The reduced form of nitric oxide, HNO/NO − , usually referred to as nitroxyl, exhibits its own unique biological activity and has significant pharmacological potential. For instance, HNO can act as a positive cardiac inotrope and lusitrope that provides great promise in the treatment of heart failure; also, as nitroxyl inhibits aldehyde dehydrogenase, it has potential as an alcoholism treatment .…”
Section: Introductionmentioning
confidence: 99%